(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
Introduction: The sexual dimorphism based on morphometric ear variables of the adult Indian population ishighly under-explored. Morphometry of external ear from other countries cannot be directly applicable to theIndian population.Aims and Objectives: This study aimed to evaluate morphometric parameters of the external ear among adultBengali population to assess sex-based differences.Materials and Method: A descriptive, cross-sectional study was conducted at the Burdwan Medical Collegeand Hospital from March 2021 to March 2022, involving 146 males and 146 females. Right (RT) and Left (LT)Auricle length (AL), Auricle Width (AW), Lobule Length (LL), and Lobule Width (LW) were measured usingvernier calipers. Auricle Index (AI) and Lobule Index (LI) were calculated. Two-tailed paired t-test was performedbetween the corresponding variables of males and females.Result: Right Auricle Length (RTAL), Auricle Width (RTAW), Lobule Length (RTLL), Lobule Width (RTLW) andLobule Index (RTLI) showed significant sexual dimorphism. Left Auricle Width (LTAW), Lobule Length (LTLL)and Lobule Width (LTLW) also showed significant differences (p <0.05).Conclusion: The result suggests significant sexual dimorphism in external ear morphometry among the Bengalipopulation. The assessment of ear morphometry using a simple and direct technique can be useful during forensicinvestigations. These preliminary findings indicate that ear morphometry can be used as a supportive tool inforensic anthropology and biometric identification.